Comparative study between spatial location and building permit authorization in Lisbon - Ricardo, R. A. D. (Sustainability and Automation in Smart Constructions, 2019)
The urban tissue of a city is not static, but rather is constantly changing due to the permanent human activity. In Portugal the right to property is defined in the 62th Article of the Portuguese Constitution; however, this right does not automatically confer the right to its transformation. It is the responsibility of the municipality for the management of the transformations in the urban tissue through urban management activities. Those are legally framed by various legal instruments where the legal regulation of urbanization and edification is the most relevant. The purpose of this study is to develop methods to analyze the relationship between the Lisbon City Council’ evaluation (authorization or rejection), on building permits (architectural design phase) between the years 2002 and 2018, and the spatial location of the building. Such an analysis enables the city hall, promoters and real estate to be informed on the impact that different territorial zones have on the building permits authorized by the city council. The enormous amount of digital data produced in the scope of the urban management activity and the lack of analysis tools makes it very difficult to achieve an objective assessment on the causes that lead to decision making. The study data from different repositories was gathered and loaded into a central Postgres database. Arcgis and PGAdmin software were used in these steps. After that, the data was enriched with values regarding the Parishes boundaries, city detail and urbanization plans, existence of allotment and built heritage protection areas. In data representation Power BI software was used. In an empirical analysis approach the study reveals evidences that the geographical location of the construction site can have influence on the building permit authorization by the city hall. However, more analysis dimensions should be included in the future to clarify on some inconclusive results.